Hook, line & singer! : essential criteria for maximising the playlist potential of New Zealand music on commercial radio : a programme directors' perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Media Studies at Massey University - Neill, Karen (Massey University, 2000)
For years the commercial radio industry in New Zealand has fought against regulation of local music on the airwaves, citing that in the competitive radio environment (a product of governmental deregulation of the industry) it would be detrimental to both their business and the present levels of local content being achieved voluntarily by radio. It is this same competition that forces commercial radio Programme Directors (PDs) to be ruthless with the music selected for their playlists. With up to 40 new releases a week and only a limited number of spaces available, every track is carefully scrutinised. Justification of decisions are made by the consideration of various selection criteria identified in this study, such as the overseas performance of a track, an artist's profile in the media, and the amount of promotional support they are receiving. Often, these qualities can supersede the sound of the song itself. 'Quality marketing is (arguably) more important than quality music. Not a palatable situation to many music people, I know, but a nasty reality and understandable when you consider the CD clutter that radio is faced with' (Smyth, pers.comm., 27 January 2000). This situation does not bode well for local musicians, many of whom come to radio without qualities such as a previous radio track record. Additionally, the number of local releases presented to radio is significantly less than the number of overseas releases, yet in order to be considered for playlist selection PDs state that local music must be judged alongside its international counterparts – in other words, by the same selection criteria. PDs do concede, however, that a local music track will be given preference over an international track of equal quality, but only if it satisfies all other selection criteria. While there is evidence to suggest that this decision is political (and perhaps being used to stem the tide of proposed music regulation), the identification of selection criteria presented in this study, combined with a PD preference for New Zealand music, could give local musicians a chance to secure a spot on the commercial radio playlist that may otherwise be difficult to obtain.
Keywords: Music trade, New Zealand; Radio stations, New Zealand; Radio programmes; Popular music; Music radio; Commercial radio, New Zealand; Local music